Nicotiana benthamiana Elicitor-Inducible Leucine-Rich Repeat Receptor-Like Protein Assists Bamboo Mosaic Virus Cell-to-Cell Movement - Chen, I.-Hsuan; Huang, Ying-Ping; Tseng, Ching-Han; Ni, Jian-Tang; Tsai, Chung-Han; Hsu, Yau-Heiu; Tsai, Ching-Hsiu (Frontiers in Plant Science, 2017)
For successful infection, a virus requires various host factors at different stages such as translation, targeting, replication, and spreading. One of the host genes upregulated after Nicotiana benthamiana infection with Bamboo mosaic virus (BaMV), a single-stranded positive-sense RNA potexvirus, assists in viral movement. To understand how this host protein is involved in BaMV movement, we cloned its full-length cDNA by rapid amplification of cDNA ends. The gene has 3199 nt and encodes a 969-amino acid polypeptide. The sequence of the encoded polypeptide is orthologous to that of N. tabacum elicitor-inducible leucine-rich repeat (LRR) receptor-like protein (NtEILP), a plant viral resistance gene, and is designated NbEILP. To reveal how NbEILP is involved in BaMV movement, we fused green fluorescent protein (GFP) to its C-terminus. Unfortunately, the gene’s expression in N. benthamiana was beyond our detection limit possibly because of its large size (~135 kDa). However, NbEILP at such low expression could still enhance BaMV accumulation in inoculated leaves. A short version of NbEILP was constructed to remove the LRR domain, NbEILP/ΔLRR-GFP; the expression of this deletion mutant could still enhance BaMV accumulation to 1.7-fold that of the control. Hence, the LRR domain in NbEILP is not an essential element in BaMV movement. We constructed a few deletion mutants — NbEILP/ΔLRRΔTMD (without the transmembrane domain), NbEILP/ΔLRRΔCD (without the cytoplasmic domain), and NbEILP/ΔLRRΔSP (without the signal peptide) — to examine whether these domains are involved in BaMV movement. For BaMV movement, NbEILP requires the signal peptide to target the endoplasmic reticulum and the transmembrane domain to retain on the membrane.